Cash holdings and business conditions - Custódio, Cláudia (2022)
We investigate the relation between business conditions and corporate liquidity decisions by US firms. We find strong evidence that financially constrained firms hold more cash during recessions and that business conditions are significant to constrained firms’ cash decisions. In contrast, we find weak evidence that financially unconstrained firms adjust cash holdings according to the business cycle. This asymmetric behavior is more pronounced for changes in the short-term interest rate. Moreover, we find that firms increase the level of liquidity during periods of tighter credit conditions. Our findings support both the precautionary motive for holding cash and the pecking order theory